Understanding the determinants and impact of the adoption of technologies for sustainable farming systems in water-scarce areas of Bangladesh - Sunny, Faruque As; Karimanzira, Taonarufaro Tinaye Pemberai; Peng, Wenhuan; Rahman, Md Sadique; Zuhui, Huang (Frontiers in Sustainable Food Systems, 2022)
Introduction Bangladesh's quest to achieve sustainable development goals has highlighted the need to enhance resilience against the challenges that interconnected food, energy, and water (FEW) nexus systems faces to support human well-being. The government has decided to promote the adoption of competent and cutting-edge technologies that can significantly contribute to balancing energy and water resource utilization in achieving a more sustainable and climate-smart food production system. Hence, scaled-up adoption of solar-powered irrigation systems and recommended fertilizer dose (SIRFD) applications were proposed. This study, to provide practical policy implications, attempts to identify the determinants and impact of SIRFD adoption in water-scarce areas of Bangladesh. Methods Determinants of adoption were analyzed using multinomial logistic regression, and the adoption impact was analyzed using treatment effect models. Results The results revealed that land typology, soil fertility perception, soil water retention, knowledge, environmental awareness, secondary income, close acquaintance adoption, and cash availability significantly influenced adoption decisions. The treatment effect model result indicated that farmers who adopted both technologies could reduce production costs by 1.36% and obtain an 8.92% higher ROI than non-adopters. Conclusion The study findings suggest that policy interventions on scaling up SIRFD adoption require focusing on knowledge development village-based demonstration activities, group farming models backed by micro-finance, and avoiding launching conflicting schemes.